Moving beyond townscape to eventscape: comparison of Lisbon and Istanbul - Kesici, Neslisah; Erkan, Nilgun Colpan; Anastasia, Caterina; Serpa, Filipa (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
The structuring effect of planned events on urban life is crucial in creating distinctive character of cities, beyond their physical environment. This study compares the eventscape of Lisbon and Istanbul, two cities with similar urban structures but distinct political, cultural, and socio-economic contexts. The study expands upon the existing frameworks to analyse how public spaces are used for events and how these events shape urban spaces. It focuses on political-economic challenges, cultural dynamics, spatial needs, and temporal patterns, examining how these factors influence event planning and space utilization. Lisbon benefits from public-private partnerships and a strong focus on community engagement, leading to the creation of accessible public spaces, especially streets. In contrast, Istanbul faces challenges related to governance and security, with a preference for large parks on the periphery. Despite these differences, both cities prioritize cultural events and aim to ensure equitable access for citizens. This study offers insights for urban policy by supporting equitable approaches that empower communities, for event management by highlighting the alignment of location selection and event programming, and for urban design by providing guidance on creating sustainable event spaces through adaptability, temporary uses, and flexible spaces.
Keywords: Event planning; public space; location selection; placemaking; comparative urban studies; Environmental Sciences & Ecology; Geography; Public Administration; Urban Studies